Benin's Infrastructure : A Continental Perspective - Dominguez-Torres, Carolina; Foster, Vivien (World Bank, Washington, DC, 2017)
Between 2000 and 2005 infrastructure made an important contribution of 1.6 percentage point to Benin's improved per capita growth performance, which was the highest among West African countries during the period. Raising the country's infrastructure endowment to that of the region's middle-income countries could boost annual growth by about 3.2 percentage points. Benin has made significant progress in some areas of its infrastructure. The rural road network is in relatively good condition, and about 30 percent of the rural population has access to an all-season road, a level above the country's peers. Air transport connectivity has improved. Also, important market liberalization reforms designed to attract private capital to the water and information and communications technology (ICT) sectors have boosted performance. In particular, increased competition in the ICT market has contributed to the rapid expansion of mobile and Internet services. Addressing Benin's infrastructure challenges will require sustained expenditures of $712 million per year over the next decade, with heavy emphasis on capital expenditure. Almost half of the total relates to the transport sector. At 16.6 percent of Benin's 2005 gross domestic product (GDP), this effort is almost at the level of other Sub-Saharan African countries. Benin already spends around $452 million per year on infrastructure, equivalent to about 10.5 percent of its GDP. Almost $101 million a year is lost to inefficiencies of various kinds, associated mainly with under pricing in the power and water sectors; poor financial management of utilities; and inefficient allocation of resources across sectors. If Benin could raise tariffs to cost-recovery levels, and reduce operational inefficiencies in line with reasonable developing-country benchmarks, it could substantially boost flows to the infrastructure sectors. Comparing spending needs with existing spending and potential efficiency gains (and assuming that the inefficiencies are fully captured) leaves an annual funding gap of $210 million per year. By far the largest share of the gap can be traced to the water supply and sanitation sectors. Benin has the potential to close this gap by adopting alternative technologies in water supply, transport and power. Savings from alternative technologies could amount to as much as $227 million per year.